Mitogen-activated protein kinases p42mapk and p44mapk are required for fibroblast proliferation. - Pagès, G (1993)
The mitogen-activated protein kinases (MAP kinases) p42mapk and p44mapk are serine/threonine kinases rapidly activated in cells stimulated with various extracellular signals by dual phosphorylation of tyrosine and threonine residues. They are thought to play a pivotal role in integrating and transmitting transmembrane signals required for growth and differentiation. Here we demonstrate that activation of these ubiquitously expressed MAP kinases is essential for growth. To specifically suppress MAP kinase activation in fibroblasts, we transiently expressed either the entire p44mapk antisense RNA or p44mapk kinase-deficient mutants (T192A or Y194F). As expected, and through independent mechanisms, both approaches strongly inhibited MAP kinase activation. The antisense reduced the expression of endogenous p42mapk and p44mapk by 90%, whereas overexpression of the T192A mutant inhibited growth factor activation of both endogenous MAP kinases by up to 70%. As a consequence, we found that the antisense as well as the T192A mutant of p44mapk inhibited growth factor-stimulated gene transcription (collagenase promoter assay with chloramphenicol acetyltransferase reporter) and cell growth. These effects were proportional to the extent of MAP kinase inhibition and reversed by coexpression of the wild-type p44mapk. Therefore we conclude that growth factor activation of p42mapk and p44mapk is an absolute requirement for triggering the proliferative response.